Falling from grace: HPRT is not suitable as an endogenous control for cancer-related studies. (4th March 2019) - Townsend, Michelle H.; Felsted, Abigail M.; Ence, Zac E.; Piccolo, Stephen R.; Robison, Richard A.; O'Neill, Kim L.
ABSTRACT: HPRT is a housekeeping enzyme involved in recycling guanine and inosine in the purine salvage pathway. As a housekeeping gene, HPRT has been widely used as an endogenous control for molecular studies evaluating changes in gene expression. Yet, recent evidence has shown that HPRT exhibits high variability within malignant samples. We designed this study to determine whether this observed upregulation is consistently found, therefore rendering hprt an unsuitable normalization control in cancer. Utilizing protein and RNA-seq expression, we found that malignant and normal patient samples vary significantly both within the same tissue type and across organ sites. Upon staining for HPRT via immunohistochemistry, we found that expression is highly variable in malignant samples (Lung; 89.2–111.8, Breast; 66.7–98.3, Colon; 85.3–129.7, Prostate; 90.8–155.4, Pancreas; 74.1–132.1). Similarly, we observed high variability across cell lines via western blotting (p < 0.0001) which was further confirmed using RNA sequencing. Comparing normal and malignant patient samples, we observed consistent upregulation of HPRT expression within malignant samples relative to normal samples (p = 0.0001). These data indicate that HPRT is unsuitable as an endogenous control for cancer-related studies because its expression is highly variable and exceeds that of an appropriate control; therefore, we recommend its discontinued use as a normalization gene.